2006
DOI: 10.1179/174329406x85056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toughness of hard coatings

Abstract: Repeated impact has been introduced to evaluate different properties of hard coatings, such as impact wear resistance, bonding strength, fatigue, etc. The load and impact number relationships are similar to that of fatigue curves, and close to some real applications of coated parts. Cr-Cu-N coatings were performed on a hardened steel substrate and the repeated impact tests were conducted on the coating substrate system. At a low impact load, the intrinsic strength of the coating layer and the bonding strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…At the macro-scale coating impact resistance is commonly evaluated in non-depth sensing tests with indenters of WC-Co, hardened steel [29] or silicon nitride [30], typically with radii of 2.5 or 3 mm [30][31][32][33][34] although smaller radii (e.g. around 1 mm) have also been used [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…At the macro-scale coating impact resistance is commonly evaluated in non-depth sensing tests with indenters of WC-Co, hardened steel [29] or silicon nitride [30], typically with radii of 2.5 or 3 mm [30][31][32][33][34] although smaller radii (e.g. around 1 mm) have also been used [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Arai et al however determined that rolling/sliding tests were more suitable for assessing coating durability than impact ("hammering") tests as the latter showed a number of coating failure mechanisms in addition to adhesive failure (flaking) [22]. Similarly, Bao et al determined that cohesive failure frequently dominated the coating response in impact tests and instead suggested that repeated impact tests be used to assess coating toughness [29]. Recently, instrumented micro/nano scale impact testing has been developed as a potential adhesion test [30].…”
Section: Interfacial Fatigue Resistance For Long-term Tribological Dumentioning
confidence: 96%
“…14 Only adhesive failure is associated with the adhesion of the coating, but the impact test always involves cohesive failure, which is related to coating toughness. 15,16 Although the adhesion measured for a hard coating under a load is close to that under service conditions, it is still difficult to detach the coating from the substrate along the interface.…”
Section: Introductionmentioning
confidence: 95%